2020
DOI: 10.1017/s1092852920001522
|View full text |Cite
|
Sign up to set email alerts
|

Head circumference in infants with nonopiate-induced neonatal abstinence syndrome

Abstract: Background No relationship has been reported between nonopiate neonatal abstinence syndrome (NAS) and anthropometric indices, including head circumference (HC). The purpose of this study was to determine the relationship between maternal nonopioid drug use and HC at birth in neonates with NAS. Methods This retrospective observational study included neonates born between January 1, 2010 and March 31, 2019, whose mothers had been taking antipsychotic, antidepressant, sedative, or anticonvulsant medications. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Exclusion criteria were as follows: (i) gestation shorter than 36 weeks; (ii) for infants: birthweight <2000 g; (iii) for mothers: drugs taken only before conception; (iv) for mothers: anticonvulsants taken alone; and (v) for infants: chromosomal abnormalities, congenital heart disease, and respiratory disorders. This is the same dataset used in our previous study, 4 and because that study reported that anticonvulsants alone did not cause NAS, anticonvulsants were excluded in this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Exclusion criteria were as follows: (i) gestation shorter than 36 weeks; (ii) for infants: birthweight <2000 g; (iii) for mothers: drugs taken only before conception; (iv) for mothers: anticonvulsants taken alone; and (v) for infants: chromosomal abnormalities, congenital heart disease, and respiratory disorders. This is the same dataset used in our previous study, 4 and because that study reported that anticonvulsants alone did not cause NAS, anticonvulsants were excluded in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical symptoms include irritability, apnea, involuntary movements, seizures, tachycardia, sweating, vomiting, and diarrhea, sometimes requiring intensive care 2 . Opioid‐induced NAS is common worldwide but psychiatric drugs are a more common cause in Japan 3,4 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging data demonstrate the adverse effects of prenatal opioid exposure on the developing brain at the macrostructural, microstructural, neurophysiological, and/or functional levels. In utero opioid exposure results in a smaller head circumference (e.g., altered brain growth), although this effect may be mediated by co-exposure to maternal tobacco or other psychoactive medications ( 44 , 61 64 ). Early studies using ultrasonography have shown enlargement of in the thalamus of exposed subjects over the first six months of life ( 65 , 66 ).…”
Section: Ongoing Management and Long-term Effects Of Nasmentioning
confidence: 99%